Trendy Drink Creations: Easy, Delicious, and Attractive for the Students Of SMK AlJabar Batam - Sipayung, Natal Olotua; Dailami; Moh. Thandzir; Tito Pratama; Yusakh Yama Langi (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
Currently, trendy beverages such as mocktails are becoming increasingly popular among teenagers, especially high school students. Mocktails are non-alcoholic drinks that are appealing due to their aesthetic appearance, attractive colors, and refreshing taste. This community service activity at SMK Aljabar Batam aims to provide education on how to create trendy drinks that are simple, delicious, and visually attractive using basic techniques such as pouring and muddling. The training also introduces various drink-making tools such as the muddler, jigger, and mixing glass. Through this program, students are expected to acquire basic skills in drink mixing, understand flavor combinations, and enhance their creativity in presentation. Moreover, this activity also aims to foster an entrepreneurial spirit, encourage independence, and open business opportunities in the creative industry sector.